Pengabdian Masyarakat di Desa Peduli Lingkungan Darat: Lestari Bukit Tegal Malaka (Penanaman Pohon dan Workshop Penyemaian dan Pembibitan di Kawasan Bukit Tegal Malaka) - Maulana, Tashdiq; Salasabilla, Salma; Vera, Nabila; Aisyah, Siti; Zakiyah, Silfa; Khoirrunisa, Anis; Firmansyah, Firmansyah; Nabila, Fiqih; Fakhri, Ziyad; Syamsyudin, Ahmad; Anggraeni, Anggi (Yayasan Cendekia Gagayunan Indonesia, 2025)
Village SDGs or Village Sustainable Development Goals, is a joint initiative to realize the Sustainable Development Goals (SDGs) at the village level. These Village SDGs are an adaptation of the global sustainable development goals that focus on poverty alleviation, reducing inequality, and environmental conservation. The goal of environmental conservation is to protect natural resources and reduce negative impacts on the environment. One effort to preserve the environment is to reforest or reforest critical land so that it returns to its original forest function. Rancabango Village faces various environmental and social problems that require serious attention. This can also be seen in the SDGs score index for the 15th Ranbidango Village Goal, namely the Land Environmental Care Village which received a score of 0.00 Based on information from the Kemendesa website. Based on this, we created the Lestari Bukit Tegal Malaka program. This program is an effort to increase the Village SDGs score regarding the goal of a land environmental care village. There are two work programs in the Lestari Bukit Tegal Malaka program, namely the reforestation program and the seedling and nursery workshop.